E-018 Initial experience with distal guide catheter placement in the treatment of cerebrovascular disease: clinical safety and efficacy. (4th July 2012) - Turk, A; Manzoor, M; Nyberg, E; Chaudry, M; Turner, R
Abstract : Background: The treatment of cerebrovascular diseases continues to grow with improvements in technology. The use of stable guide catheters in the large cervical cerebral vessels has historically been paramount to the success of endovascular procedures. Advancements in technology over the last several years has created a new generation of guide catheters that can continue to provide stable access, but navigate portions of the tortuous carotid siphon to allow more distal access. We reviewed our clinical experience over the last 4 years with the release of these new guide catheters to determine the safety and efficacy of their use in everyday clinical practice. Methods: Between October 2007 and November 2011, all therapeutic Neurointerventional procedures that were performed at our institution were reviewed. We excluded any cases where guide catheter support was not critical to the success of the surgery or when there was inadequate documentation of the anatomy traversed by the catheter. This included ECA embolizations, cervical carotid or extracranial vertebral artery stenting, or any case without cervical vessel angiography. We retrospectively reviewed the images and procedure reports to determine the success of achieving distal intracranial access and any guide catheter related complications with the newer generation guide catheter. The final location of the guide catheter tip was documented and success determined by the number of 90° turns the catheter was able to negotiate. The larger 0.070″ caliber guide catheters were judged to be successful by navigating 1 or more turns and 0.053″ and smaller catheters had to navigate two or more turns. Results: 1185 therapeutic Neurointerventional procedures were performed, of which 659 were eligible for this study. Distal access into the intracranial circulation was successful 70% of the time in 397 cases utilizing 0.070″ guide catheters. The 0.070″ guide catheters were able to navigate at least one sharp turn in 79% of cases. The Neuron 0.070″ catheter was used 62% of the time and was successful at reaching the intracranial vessels 81%. The 6F Chaperone was used 38% of the time and was successful 57% of the time. The 0.053″ guide catheters were successful navigating at least two sharp turns in 61% of 132 cases and reached the intracranial circulation in 74% of cases. The Neuron 0.053″ catheter was used 75% of the cases and was successful in navigating at least two sharp turns 68% of the time. The Chaperone 5F guide catheter was used 25% of the time and was successful 39% of the time. Guide catheter related complications were encountered in 1.4% of cases with both traditional and current generation catheters and differences were not significant. Significantly more complications were found when guide catheter tip position was cervical rather than intracranial and when cases were performed emergently rather than in the elective setting. Conclusion: Current generation guide catheters allow distal access with a high rate of success while maintaining a low rate of complications. When intracranial location of the guide catheter was obtained, fewer complications occurred. Competing interests: None.